Decision Support Software for Soybean Growers: Analyzing Maturity Group and Planting Date Tradeoffs for the US Midsouth. Issue 1 (28th December 2016) - Popp, Michael; Purcell, Larry; Salmerón, Montserrat
Abstract : Core Ideas: Modifying maturity group and planting date in soybean affects yield potential, yield risk, phenology, soybean price, and irrigation needs. Choosing among a set of 14 planting dates and 8 relative maturity groups is complex. Decision support software can help compare between relative maturity groups. Among other choices, soybean [ Glycine max (L.) Merr.] producers in the Midsouthern United States face decisions regarding the optimum maturity group (MG) to select for a given planting date and location. From a profitability perspective, weather‐driven irrigation water needs and harvest date implications on seasonal sale price complicate planting choices. Using a large set of experimental trials conducted across 10 locations in the Midsouth, the DSSAT‐CROPGRO‐Soybean crop simulation model was validated. Thereafter, the model was used to create a database of simulated 30‐year yield and irrigation water needs based on past weather data for 13 locations. With that data, a spreadsheet‐based tool was developed to compare soybean planting strategies by selecting from 2 soil textures, 14 different planting weeks, and 8 relative maturity group (rMG) choices ranging from rMG 3.0 to 3.4 to rMG 6.5 to 6.9 in 0.5‐rMG intervals at each location. User‐specific comparisons allow insights on yield potential, yield risk, phenology, irrigation needs, soybean price, and irrigation cost sensitivity analysis as well as profitability assessment across MGs and planting dates.